Interface Defect Hydrogen Depassivation and Capacitance-Voltage Hysteresis of Al2O3/InGaAs Gate Stacks - Tang, Kechao (2017)
We investigate the effects of pre- and postatomic layer deposition (ALD) defect passivation with hydrogen on the trap density and reliability of Al2O3/InGaAs gate stacks. Reliability is characterized by capacitance-voltage hysteresis measurements on samples prepared using different fabrication procedures and having different initial trap densities. Despite its beneficial capability to passivate both interface and border traps, a final forming gas (H2/N2) anneal (FGA) step is correlated with a significant hysteresis. This appears to be caused by hydrogen depassivation of defects in the gate stack under bias stress, supported by the observed bias stress-induced increase of interface trap density, and strong hydrogen isotope effects on the measured hysteresis. On the other hand, intentional air exposure of the InGaAs surface prior to Al2O3 ALD increases the initial interface trap density (Dit) but considerably lowers the hysteresis.